A trans-holocene approach to assess maritime development on the California Channel Islands archipelago: A case study from Eel Point, San Clemente island. (30th September 2021) - Gusick, Amy E.; Perry, Jennifer; Gill, Kristina; Teeter, Wendy
Abstract: The Channel Islands of California have received much attention from researchers, in part, due to the long occupation history of the islands that spans at least 13, 000 years. The Northern Channel Islands have played an important role in our understanding of early coastal adaptations and development of complexity among maritime adapted peoples; however, this is only part of the picture. The Southern Channel Islands, located approximately 90 km south of the Northern Channel Islands, have a similar occupational history to their northern counterparts, but exist in a very different environmental and geographic context. Occupants on each island would have faced marine and terrestrial environments that could be vastly different based on issues such as fluctuating sea temperatures, fresh water accessibility, and plant, animal, and marine shell seasonality. The coastal adaptations along all the Channel Islands reflected these differences. Understanding variation on the Channel Islands archipelago can be realized by comparing and contrasting multiple types of environmental and material data from trans-Holocene sites, archaeological deposits that present continuous data sequences over a wide time span of the Holocene. One such site from San Clemente Island in the southern portion of the archipelago is Eel Point. Previous excavations at this site resulted in a rich array of cultural material; however, recent research has shown major portions of the collections have not yet been processed, are unanalyzed, or are under-analyzed. Specifically the groundstone and archaeobotanical assemblages have not been comprehensively analyzed or reported on, but are integral to understanding not only subsistence strategies, but also technological development and island paleo and historical ecology. These data form the basis for an inter-island comparative approach to understand long-term human-environmental interactions and impacts to ancient ecosystems on the Channel Islands archipelago. This study focuses on leveraging these under-analyzed and unanalyzed data to present on the variation in adaptions on the archipelago and to demonstrate the relevance of multi-island studies for considering the cultural impacts of climatic change in Mediterranean environments.